Islamic Youth Education Curriculum In The Qur'an - Andri Setiadi; Salman Salman (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
Youth are agents of change, their existence determines the fate of a nation, whether or not a country will suffer in the future depends on its youth today. This is because youth have more privileges than other age groups. Among these features are the ability of reason and strong body, which has the potential to support the influence he can carry. The brilliance of the Islamic era that we still feel today is a major contribution of Muslim youth in the past. So that what educators have done in the past for their youth is urgent to be studied. Likewise, in the holy book Al-Qur'an, there are many stories of youth, including the story of the youth of Ashabul Kahf, the story of the Prophet Yusuf when he was young and the story of the Prophet Ibrahim when he was young. They are the figures of tough youths who are able to change the society of their time. And when examined further, the success of these youths stems from a straight and true belief in Allah SWT, the strong monotheism in their hearts is what gives great strength and strong motivation in inviting their people to the straight path, namely the way of worshiping Allah alone. .